Zapisz w jak najprostszej postaci :
a) 3x - 2xy + 5x =
b) (5x - 7y) - (3y - 7x ) =
c) -(a - 2b) -2 (b - 2a ) =
d) 3(x - 2y) -2 ( y - 3x ) =

DANE SĄ SUMY ALGEBRAICZNE A: 2x - 3y , B: 2y - 3x , C: 2x + 3y
A - B =
B - A =
C - A =
B - ( A + C ) =
A - ( B - C ) =

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-02T18:59:10+01:00
Zad.1
a) 3x - 2xy + 5x = x ( 3 - 2y + 5 )
b) (5x - 7y) - (3y - 7x ) = 5x - 7y - 3y + 7x = 12x - 10y = 2 ( 6x - 5y )
c) -(a - 2b) -2 (b - 2a ) = -a + 2b - 2b + 4a = 3a
d) 3(x - 2y) -2 ( y - 3x ) = 3x - 6y - 2y + 6x = 9x - 8y

zad.2
A-B = 2x - 3y - 2y + 3x = 5x - 5y
B-A = -2y - 3x - 2x +3y = y - 5x
C-A = 2 + 3y - 2x + 3y = 6y
B - ( A + C ) = 2y - 3x - (2x - 3y + 2x + 3y) = 2y - 7x
A - ( B - C ) = 2x - 3y - 2y + 3x + 2x + 3y = 7x - 2y
39 3 39
2009-11-02T22:26:49+01:00
A)
3x - 2xy + 5x =8x - 2xy
b)
(5x - 7y) - (3y - 7x ) = 12x -10y
c)
-(a - 2b) -2 (b - 2a ) = 5a -4b
d)
3(x - 2y) -2 ( y - 3x ) = 9x -4y


A - B = 2x-3y-(2y-3x)= -1x -5y

B - A = 2y-3x -2x-3y= -1y -5x

C - A = 2x + 3y -2x - 3y =0

B - ( A + C ) = 2y - 3x -(2x - 3y + 2x + 3y )=12x+2y

A - ( B - C ) = 2x - 3y-(2y - 3x- 2x + 3y )=-3x-2y

Pozdrawiam
9 3 9